Desenvolvimento de um chaveador baseado em topologia spdt associado a sensores interdigitados para medicao de parametros de capacitancia e impedancia em misturas pseudobinarias diesel/biodiesel - ANDRADE, Cassio Daniel Salomao Silva (2019)
The increasing addition of biodiesel to diesel has reached significant market importance and methods for detecting these levels, in these blends, have been essential in the monitoring of their quality. In this context, it is proposed the design, construction and evaluation of an 8- channel microcontrolled switcher based on miniature electromechanical armature relays that, in association with an LCR meter, allows the measurement of capacitance and impedance parameters in multiple diesel/biodiesel blend samples, using, for this purpose, an interdigitated electrode to investigate the feasibility of multiple measurements of these parameters and to evaluate the applicability of this methodology in the detection of biodiesel contents in those samples. A functional test to determine the mean percentage errors and measurement uncertainties associated with each switcher channel, relatively to reference values – obtained with an ordinary capacitor directly connected to the LCR bridge terminals –, as well as a significance test to evaluate the differences between the the measured values with and without interposing switcher were performed. It is suggested, subsequently, an apparatus for detection of organoleptic patterns in substances (electronic tongue/nose), electrochemical and/or biochemical (electronic probing device).